Enhancing the in vitro and in vivo activity of itraconazole against breast cancer using miltefosine-modified lipid nanocapsules - Nabila A. El-Sheridy; Riham M. El-Moslemany; Alyaa A. Ramadan; Maged W. Helmy; Labiba K. El-Khordagui (Taylor & Francis Group, 2021)
Itraconazole (ITC), a well-tolerated antifungal drug, exerts multiple anticancer effects which justified its preclinical and clinical investigation as potential anti-cancer agent with reduced side effects. Enhancement of ITC anti-cancer efficacy would bring valuable benefits to patients. We propose herein lipid nanocapsules (LNCs) modified with a subtherapeutic dose of miltefosine (MFS) as a membrane bioactive amphiphilic additive (M-ITC-LNC) for the development of an ITC nanoformulation with enhanced anticancer activity compared with ITC solution (ITC-sol) and unmodified ITC-LNC. Both LNC formulations showed a relatively small size (43-46 nm) and high entrapment efficiency (>97%), though ITC release was more sustained by M-ITC-LNC. Cytotoxicity studies revealed significantly greater anticancer activity and selectivity of M-ITC-LNC for MCF-7 breast cancer cells compared with ITC-sol and ITC-LNC. This trend was substantiated by in vivo findings following a 14 day-treatment of murine mammary pad Ehrlich tumors. M-ITC-LNC showed the greatest enhancement of the ITC-induced tumor growth inhibition, proliferation, and necrosis. At the molecular level, the tumor content of Gli 1, caspase-3, and vascular endothelial growth factor verified superiority of M-ITC-LNC in enhancing the ITC antiangiogenic, apoptotic, and Hedgehog pathway inhibitory effects. Finally, histopathological and biochemical analysis indicated greater reduction of ITC systemic toxicity by M-ITC-LNC. Superior performance of M-ITC-LNC was attributed to the effect of MFS on the structural and release properties of LNC coupled with its distinct bioactivities. In conclusion, MFS-modified LNC provides a simple nanoplatform integrating the potentials of LNC and MFS for enhancing the chemotherapeutic efficacy of ITC and possibly other oncology drugs.